Analisis Kontribusi Pajak Kendaraan Bermotor Terhadap Pendapatan Asli Daerah - Stenly Almendo Waisapy; Trudy Maryona Nussy (Jurnal Administrasi Terapan, 2024)
This study analyzes the contribution of Motor Vehicle Tax to the Regional Original Revenue of Maluku Province for the period 2019-2023. The analysis technique used is contribution analysis, by compare the relationship of motor vehicle tax revenue with the total of Local Original Income of Maluku Province. The findings indicate that despite a decline in revenue realization due to the COVID-19 pandemic on 2020, the contribution of Motor Vehicle Tax to Local Original Income remained consistently high. The percentage contribution of Motor Vehicle Tax for each year is as follows: 79.78% in 2019, 71.35% in 2020, 76.61% in 2021, 79.08% in 2022, and 80.86% in 2023. This findings indicate the significance of Motor Vehicle Tax as a vital source of regional revenue and highlight the regional government's efforts to enhance public awareness and compliance regarding tax payment obligations.Keywords: contribution, motor vehicle tax, regional original revenue